Efficacy of scorpion antivenom plus prazosin versus prazosin alone for Mesobuthus tamulus scorpion sting envenomation in children: a randomised controlled trial. Issue 6 (18th February 2014) - Pandi, Karuppiah; Krishnamurthy, Sriram; Srinivasaraghavan, Rangan; Mahadevan, Subramanian
Abstract : Objective: To assess the efficacy of combined use of scorpion antivenom (SAV) with prazosin, compared with prazosin alone in children with Mesobuthus tamulus scorpion envenomation. Study design: Randomised controlled trial. Setting: A tertiary care hospital in south India. Patients: 50 children with definite history and/or systemic manifestations of scorpion envenomation were recruited from the paediatric emergency or outpatient department from February 2012 to July 2013. Interventions: The children were randomised into two groups. In 25 children, SAV was administrated as a slow intravenous bolus combined with prazosin (group A). Others received prazosin alone (group B). Results were analysed by Student t test and χ 2 test. Main outcome measures: Time required for resolution of autonomic symptoms, total dose of prazosin, adverse events. Results: Children in group A recovered earlier than those in group B (mean difference 9.1 h, 95% CI 6.0 to 12.2). 23 children (92%) in group A were clear of autonomic symptoms within 10 h, compared with 10 children (40%) in group B (mean difference 52%, 95% CI 29% to 75%). The proportion of children deteriorating to clinical grade 3 or 4 was 8% in group A as against 44% in group B (p<0.01). The mean dose of prazosin required was 54 µg/kg versus 130.8 µg/kg in group A and B, respectively (p<0.01). SAV was not associated with severe adverse reactions. Conclusions: Usage of SAV led to faster recovery and reduced the incidence of myocardial dysfunction. Combined therapy with SAV and prazosin is beneficial for children with M tamulus scorpion envenomation. Trial registration number: CTRI/2013/09/004002 (Clinical Trials Registry of India).